Simplify management of security and compliance with IBM PowerSC in cloud and virtualized environments - Quintero, Dino (IBM redbooks., 2019)
This IBM® Redbooks® publication provides a security and compliance solution that is optimized for virtualized environments on IBM Power Systems"!servers, running IBM PowerVM® and IBM AIX®. Security control and compliance are some of the key components that are needed to defend the virtualized data center and cloud infrastructure against ever evolving new threats. The IBM business-driven approach to enterprise security that is used with solutions, such as IBM PowerSC"! makes IBM the premier security vendor in the market today. The book explores, tests, and documents scenarios using IBM PowerSC that leverage IBM Power Systems servers architecture and software solutions from IBM to help defend the virtualized data center and cloud infrastructure against ever evolving new threats. This publication helps IT and Security managers, architects, and consultants to strengthen their security and compliance posture in a virtualized environment running IBM PowerVM